Look east, cross black waters : India's interest in Southeast Asia - Blank, Jonah (Research report (Rand Corporation), 2015)
"The global security interests of India and the United States overlap far more than they clash, and this is particularly the case in Southeast Asia. India's core goals for Southeast Asia are all in basic harmony with those of the United States -- including regional stability; prevention of any outside nation from dominating the politics or economy of the region; peaceful settlement of territorial disputes such as the South China Sea; secure shipping through the Straits of Malacca and other crucial transit points; increased land, sea and air connectivity infrastructure; Myanmar's democratic transition; and containment of radicalism in states including Indonesia and Malaysia. But America should not expect India to enter any sort of alliance (formal or de facto), nor join any coalition to balance against China. This does not indicate an anti-American outlook, but a determination to engage with Southeast Asia at a pace and manner of India's own choosing -- and a deep caution about precipitating conflict with Beijing. The replacement of a Congress Party government with a Bharatiya Janata Party administration in May 2014 has resulted in a recalibration of India's foreign policy, but not a radical shift in its overall direction. For U.S. policymakers in the security arena, the challenge in building cooperation with India in Southeast Asia will boil down to four elements: (1) understanding India's own goals for the region better, (2) adopting strategic patience in working at a pace and manner comfortable to India, (3) finding specific areas on which to focus attention, such as technology transfer, humanitarian assistance/disaster relief, Andaman and Nicobar Islands, and Myanmar policy, and (4) moving forward, laying the foundation for future progress"--Publisher's web site